Assessment of services provided by urban ASHAs to mothers of urban slums in Lucknow district – A cross-sectional study - Santosh Kumar; Monika Agarwal; H Dinesh Kumar (Journal of Family Medicine and Primary Care)
Context: Maternal and child health is an important public health issue which indicates the level of socioeconomic development in any country. Urban accredited social health activist (U-ASHA) workers in India are the main front-line urban health workers in primary health care delivery for slum and urban poor. Aims: To assess the services provided by U-ASHA workers to mothers of urban slums for antenatal and postnatal care. Settings and Design: Cross-sectional study in urban slums of Lucknow where recently delivered women (up to 2 years) were selected. Methods and Material: To include the desired sample size of 320 recently delivered women (RDW), the U-ASHAs of the selected slums were contacted and a list of RDWs was made for each slum. By simple random sampling, 20 RDWs were selected from each slum. A predesigned and pretested interview schedule was used for data collection. Statistical Analysis Used: SPSS-version-26 was used. P <0.05 was considered statistically significant. Results: The registered pregnancies were 95%. Only 43.1% of RDW had at least four ANC visits. The institutional delivery was 84.7%. Only 27.7% of RDW visited health facilities for PNC services. About 39.4% received Janani Suraksha Yojana incentives. Contraceptive users were only 41.9%. Counseling by U-ASHA workers regarding all the ANC and PNC services had better utilization among counseled RDW except for child-care counseling. Conclusions: Counseling services regarding ANC and PNC services have a significant impact on their utilization. Better results can be achieved if the counseling by U-ASHA is enhanced to reach out more beneficiaries.